Struktur Intrinsik Al-Qur’an: Tawaran atas Kritik Analisis Retorika Semit Al-Qur’an Michel Cuypers - Andriani; Cipta Bakti Gama (Canonia Religia, 2024)
Michel Cuypers, in his book The Composition of the Qur'an: Rhetorical Analysis (2012), proposes that the Al-Qur’an is a book arranged in a very neat rhetorical series.  This is contrary to the opinion of critics of the Qur'an, such as Voltaire, Theodor Nöldeke, Thomas Carlyle, and Richard Bell, who stated that the Qur'an is not a consistent book in its composition.  Cuypers refuted their opinion by using the Semitic rhetorical analysis method on the text of the Qur'an. They proved that the Qur'an verses were not arranged haphazardly but neatly in a ring-shaped structure (ring composition). However, Cuypers' work was criticized for positioning the Qur'an as an ordinary Semitic text, contrary to the Muslim belief that the Qur'an is a unique Arabic text.  This article criticizes the Semitic rhetorical analysis method in the Al-Qur’an by proposing a new text analysis method based on the unique language of the Al-Qur’an and the logical relationships found in its verses. Using this method, it was found that the intrinsic structure of the Qur'an is in the form of a concept tree, not in the form of a ring, as claimed by Cuypers. This finding also shows the strength of coherence in the Al-Qur’an. It can add to methods for interpreting the Al-Qur’an based on logical relationships between verses as proposed by Al Ghazali in the book Al-Qistās Al-Mustaqīm.